1986
DOI: 10.1037/0033-2909.100.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Gender and aggressive behavior: A meta-analytic review of the social psychological literature.

Abstract: According to our social-role theory of gender and helping, the male gender role fosters helping that is heroic and chivalrous, whereas the female gender role fosters helping that is nurturant and caring. In social psychological studies, helping behavior has been examined in the context of short-term encounters with strangers. This focus has tended to exclude from the research literature those helping behaviors prescribed by the female gender role, because they are displayed primarily in long-term, close relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

101
810
8
27

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,033 publications
(946 citation statements)
references
References 83 publications
101
810
8
27
Order By: Relevance
“…A side effect of this could be a greater propensity to identify with the victim. This result also seems to be in line with the general consensus in aggression research that female aggression is qualitatively different with at least less overt physical cruelty (Bettencourt & Miller, 1996;Eagly & Steffen, 1996). However, the influence of gender stereotypical socialization pro cesses has been discussed as one explanation for the reported differ ences, rather than biological differences between both sexes (Archer & Mehdikhani, 2003;Archer & Parker, 1994).…”
Section: Victim Identificationsupporting
confidence: 88%
“…A side effect of this could be a greater propensity to identify with the victim. This result also seems to be in line with the general consensus in aggression research that female aggression is qualitatively different with at least less overt physical cruelty (Bettencourt & Miller, 1996;Eagly & Steffen, 1996). However, the influence of gender stereotypical socialization pro cesses has been discussed as one explanation for the reported differ ences, rather than biological differences between both sexes (Archer & Mehdikhani, 2003;Archer & Parker, 1994).…”
Section: Victim Identificationsupporting
confidence: 88%
“…), differences were found in relation to Schadenfreude. Based on studies which have found that men engage in more aggressive behaviors than women, not just physically but verbally also (Eagly & Steffen, 1986;Etxebarria et al, 2003;Tangney & Dearing, 2002), we hypothesized that women would score lower in these two variables which involve a large dose of hostility. However, despite the fact that women scored lower in both emotional variables, the difference was only significant in the case of Schadenfreude.…”
Section: Gender Differences In Empathy Negative Emotions Towards Thomentioning
confidence: 99%
“…Earlier literature reviews (e.g., Maccoby & Jacklin, 1974;Terman& Tyler, 1954) tend to emphasize biological contributions to this difference more strongly than do later ones (e.g., Eagly & Steffen, 1986;Frodi et al, 1977;Hyde, 1984), and in more recent reviews, some scholars seriously question whether biology plays an important role in human aggression (e.g., Adams, 1992;Benton, 1992). Whatever role biological factors play, contemporary theorists argue that gender roles and cultural norms contribute to gender differences in aggression (e.g., Bandura, 1973;B.…”
mentioning
confidence: 99%
“…Whatever role biological factors play, contemporary theorists argue that gender roles and cultural norms contribute to gender differences in aggression (e.g., Bandura, 1973;B. A. Baron & Richardson, 1994;Berkowitz, 1989;Dollard, Doob, Miller, Mowrer, & Sears, 1939;Eagly & Steffen, 1986;Lightdale & Prentice, 1994;Maccoby & Jacklin, 1974;Zillman, 1979). In their meta-analysis A preliminary report of this research was presented at the meeting of the Midwestern Psychological Association, May 1993.…”
mentioning
confidence: 99%
See 1 more Smart Citation